Beginning power BI : practical guide to self-service data analytics with Excel 2016 and Power BI Desktop - Clark, Dan. (New York : Apress, 2022)
Analyze your company's data quickly and easily using Microsoft's latest tools. You will learn to build scalable and robust data models to work from, clean and combine different data sources effectively, and create compelling visualizations and share them with your colleagues. Author Dan Clark takes you through each topic using step-by-step activities and plenty of screen shots to help familiarize you with the tools. This second edition includes new material on advanced uses of Power Query, along with the latest user guidance on the evolving Power BI platform. Beginning Power BI is your hands-on guide to quick, reliable, and valuable data insight. --
1. Introducing Power Pivot -- 2. Importing data into Power Pivot -- 3. Data munging with Power Query -- 4. Creating the data model -- 5. Creating calculations with DAX -- 6. Creating measures with DAX -- 7. Incorporating time intelligence -- 8. Data analysis with pivot tables and charts -- 9. Introducing Power BI Desktop -- 10. Creating reports with Power BI Desktop -- 11. Publishing reports and creating dashboards in the Power BI Portal -- 12. Creating a complete solution -- 13. Advanced topics in Power Query -- 14. Advanced topics in Power BI.
Includes index.
Keywords: Microsoft Excel (Computer file); Microsoft PowerPivot (Computer file); Business intelligence -- Computer programs; Information visualization -- Computer programs; Business -- Data processing; Visual analytics; Building interactive reports and dashboards with power bi desktop